Kerinci Language Phonological Interferences in Indonesian - Susmita, Nelvia; Ramadhan, Syahrul; Mukhaiyar, Mukhaiyar; Wahyuni, Sinta (Universitas Jambi, Indonesia, 2023)
This research aimed to find out what phonological interference is used by Indonesian Language Education Study Program students in narrative texts, what factors cause Kerinci language interference in Indonesian, and how phonological interference is used by students in narrative texts based on a gender perspective. It was qualitative with a descriptive method. The research informants were 23 STKIP Muhammadiyah Sungai Penuh students. In collecting data, the researchers used document studies and interviews. In addition, the data analysis techniques consist of 3 ways: (1) collecting data, (2) reducing data, and (3) concluding. The results showed phonological interference in 13 consonant and 11 vowel change data. The interference based on a gender perspective found that male students made fewer errors in writing narratives than female students. Furthermore, from the interview results, four factors caused Kerinci language phonological interference in Indonesian in student narrative texts: bilingual or multilingual speakers of words and languages; geographical influence of the Kerinci area; the factor of the large number of literary works from the Kerinci area; and the popularity of using Kerinci as the first language of students and regional communities in general.